Activity Book Design of Color Introduction for Mild and Moderate Intellectual Disabilities Student - Fionarizoca, Avierry; Ratri, Dianing (Gorga : Jurnal Seni Rupa, 2025)
Every child, regardless of their unique circumstances, is entitled to an education. Education has the potential to help children with special needs develop their skills and capabilities. Therefore, it is crucial to have an inclusive education that addresses the needs of children with special needs to reveal their talents and promote independence. This media aims to investigate the types of interactions that can enhance the teaching and learning experience for students with mild to moderate intellectual disabilities, particularly in understanding colors. The approach used involves Participatory Design and Participatory Action Research, where both teachers and students participate actively. This method begins with identifying needs, collecting data, conducting trials and assessments, prototyping, collaborating, making revisions, implementing, and finally performing follow-up evaluations. The goal is to create an engaging medium that improves the fine motor skills of students with mild and moderate intellectual disabilities by introducing them to the colors of a rainbow. The activities in this workbook focus on individually recognizing colors without distractions to help maintain attention. After that, students will identify colors by spelling their names that correspond to the colors displayed. This is further supported by highlighting the letters according to the colors, which helps develop fine motor skills through writing. The next task involves matching images with colors. Finally, a color-sorting exercise is conducted based on shape and color. This cycle is repeated over three consecutive days to allow students to observe and understand the colors in their environment as related to those in the rainbow. Through these activities, students with mild intellectual disabilities can name colors and memorize the order of the rainbow to identify colors around them. For students with moderate intellectual disabilities, this activity helps them recognize and name nearby colors using the rainbow colors, with support and guidance from teachers.